Streamlined production of immobilized D-psicose 3-epimerase via secretion in Pichia pastoris: a new paradigm for industrial D-psicose production - Pimsiriya Srila; Phitsanu Pinmanee; Boontiwa Ninchan; Nisit Watthanasakphuban (Microbial Cell Factories)
Abstract Background D-psicose, a rare sugar with significant health benefits, holds great promise as a low-calorie sweetener. Its synthesis requires the enzyme called D-psicose 3-epimerase (DPEase), which converts D-fructose into D-psicose. This study focuses on an alternative protein expression system for secretion DPEase production, using Pichia pastoris KM71. The gene encoding DPEase from Bacillus sp. KCTC 13219 was codon-optimized and fused downstream of the α-factor signal peptide. A one-step purification and immobilization method was developed by directly binding crude DPEase to a His-tag affinity column, enhancing both enzyme stability and reusability. Results The recombinant DPEase was successfully expressed in P. pastoris and efficiently secreted into the culture medium, simplifying downstream processing. The purified DPEase exhibited optimal activity at pH 6.0 and 60 °C, demonstrating remarkable thermostability and maintaining over 80% relative activity across a broad pH range (pH 5.0–11.0) and temperature range (35–70 °C). Purification with 200 mM imidazole elution resulted in a 12.54-fold increase in the purification factor, achieving a specific activity of 3.65 Units/mg. The maximum D-psicose conversion rate of purified DPEase was 17.03% at 120 min reaction with 10% (w/v) D-fructose. The developed DPEase immobilization system showed high binding efficiency, facilitating one-step purification and immobilization for ready-to-use DPEase column. The immobilized enzyme could be reused up to five cycles, maintaining 83.38% relative activity, highlighting the potential of this system for efficient D-psicose production. Conclusions This study successfully developed a prototype system for extracellular DPEase production in a recombinant microorganism. This streamlined enzyme purification and immobilization, significantly reducing the DPEase production costs. The recombinant DPEase exhibited remarkable stability across a wide range of pH and temperature. This broad stability makes the enzyme highly promising for industrial-scale D-psicose production, resulting in reduced energy costs and simplified synthesis process. The DPEase demonstrated desirable properties for various D-psicose conversion conditions, and the immobilized enzyme exhibited efficient reusability. These findings support the potential application of this system for large-scale production of D-psicose, a rare sugar with promising uses in the food and pharmaceutical industries.